Identification Species of Myxobolus from Gill of Cyprinus carpio in East Java (IDENTIFIKASI MYXOBOLUS SP YANG DIPEROLEH DARI INSANG IKAN KARPER DI JAWA TIMUR) - Priyono, Agus; ., Kurniasih; Widayanti, Rini; Nurekawati, Ayuda Dyah (Jurnal Veteriner, 2013)
The aim of study was to identify  Myxobolus sp. obtained from the gills of carp (Cyprinus carpio) ofEast Java, Indonesia. The cysts containing spores were collected from the gills of carp fish. The spores wereexamined by wet mounts preparation, fixed with ethanol absolute solution for molecular analysis. Thespores had a transparent membrane, the shell, composed of two valves. The sutural ridge running betweenthe valves. It was two anterior polar capsules, each consisted of a coiled polar filament. An iodinophilicvacuole and sporoplasm nuclei was located in posterior part. DNA Sequenses 18S rDNA followed byphylogenetic tree demonstrated that Myxobolus sp from Blitar was different from Myxosoma cerebralis ofthe Gene Bank. Myxosoma cerebralis was not found  in the fresh water fish in Indonesia.
Keywords: Myxobolus sp, Cyprinus carpio